2007
DOI: 10.1186/1749-799x-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Femoral tunnel placement in anterior cruciate ligament reconstruction: rationale of the two incision technique

Abstract: Endoscopic anterior cruciate ligament (ACL) reconstruction can be performed through oneincision or two-incision technique. The current one-incision endoscopic ACL single bundle reconstruction techniques attempt to perform an isometric repair placing the graft along the roof of the intercondylar notch, anterior and superior to the native ACL insertion. However the ACL isometry is a theoretical condition, and has not stood up to detailed testing and investigation. Moreover this type of reconstruction results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 30 publications
0
29
0
4
Order By: Relevance
“…Multiple studies have evaluated pediatric patients who were treated nonoperatively after intrasubstance ACL injuries. 8,9,21 These findings were consistent and included decreased levels of activity, recurrent episodes of instability, subsequent meniscal tears, and degenerative changes. Similar studies compared outcomes in nonsurgically versus surgically treated patients and found higher functional outcome scores, fewer episodes of instability, and decreased secondary meniscal tears in the surgically treated groups.…”
Section: Discussionmentioning
confidence: 63%
“…Multiple studies have evaluated pediatric patients who were treated nonoperatively after intrasubstance ACL injuries. 8,9,21 These findings were consistent and included decreased levels of activity, recurrent episodes of instability, subsequent meniscal tears, and degenerative changes. Similar studies compared outcomes in nonsurgically versus surgically treated patients and found higher functional outcome scores, fewer episodes of instability, and decreased secondary meniscal tears in the surgically treated groups.…”
Section: Discussionmentioning
confidence: 63%
“…This finding is in accordance with previous studies indicating that the lower graft could better control the rotational stability in single-bundle ACL reconstructions. 15,21,23,26 In this study, the deficient AM knee manifested significant laxity in AP and rotatory stability, when compared with the intact knee, so even with an intact PL bundle the knee's kinematics would still be significantly affected. The AM and PL bundles both function to maintain the knee stability, and one cannot compensate for the loss of the other.…”
Section: Discussionmentioning
confidence: 89%
“…Achieving anatomic graft placement remains a concern in ACL reconstruction (Bedi 2009; Scanlan 2009; Steiner 2009; Kopf 2010; Scanlan 2010), with studies often citing anterior and proximal placement on the femur as a problem (Kohn 1998; Arnold 2001; Garofalo 2007; Harner 2008; Kaseta 2008; Abebe 2009). This study used biplanar fluoroscopy and MR imaging to compare the effect of graft placement on the ability of ACL reconstruction to restore normal knee motion during a quasi-static lunge.…”
Section: Discussionmentioning
confidence: 99%